The validity and reliability of quality of life questionnaires in patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis: a systematic review and meta-analysis - Qian He; Jing Luo; Jiaqi Chen; Jianying Yang; Chuanhui Yao; Caiqin Xu; Qingwen Tao (Health and Quality of Life Outcomes, 2022)
Abstract Background Patients who suffered from ankylosing spondylitis (AS) or non-radiographic axial spondyloarthritis (nr-axSpA) often have poor quality of life (QoL) and there has been a substantial increase in research on acceptable questionnaires for assessment of QoL. This systematic review aims at examining the validity and reliability of QoL questionnaires in patients with AS/nr-axSpA. Methods Randomized controlled trials (RCTs), cohort trials, and cross-sectional trails were retrieved by searching seven databases. Primary outcomes included test–retest reliability and construct validity. Secondary outcomes included internal consistency, structural validity, responsiveness and so on. Data extraction and analyses were conducted according to the Cochrane standards. The Agency for Healthcare Research and Quality (AHRQ) checklists was used to assess the risk of bias for each included study. We used the Consensus-based Standards for the Selection of Health Status Measurement Instruments (COSMIN) to assess the methodological quality and measurement property of included instruments. The quality of evidence on pre-specified outcomes were assessed by the Grades of Recommendations, Development and Evaluation (GRADE) approach. Results 22 publications containing 10 self-rating instruments were included in this study. Most studies were cross-sectional in design and a total of 3,085 participants were enrolled. 19 studies had moderate to high test–retest reliability. Cronbach’s alpha (α) Coefficients were generally high (0.79–0.97) for overall scales. The ankylosing spondylitis quality of life (ASQOL) and evaluation of ankylosing spondylitis quality of life (EASi-QoL) questionnaires showed the strongest measurement properties in high-quality studies. The correlation coefficient for test–retest reliability of the ASQOL questionnaire was 0.85 (95% CI 0.80 to 0.89). The pooled Cronbach’s α coefficients of the ASQOL questionnaire and the EASi-QoL questionnaire were high. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) were considered as two validity criteria. For the ASQOL and EASi-QoL questionnaire, pooled convergent validity associations with BASDAI and BASFI were low to strong (0.24–0.81). Conclusions This study indicated acceptable reliability and stability of included QoL questionnaires. The ASQOL and the EASi-QoL questionnaires are validated and reliable disease-specific questionnaires for the assessment of QoL in patients with AS/nr-axSpA.